2015
DOI: 10.1371/journal.pone.0123305
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin Suppresses Tumor Malignancy through Inhibiting Multiple Src-Related Signaling Pathways in Non-Small Cell Lung Cancer

Abstract: Non-small cell lung cancer is the predominant type of lung cancer, resulting in high mortality worldwide. Digoxin, a cardiac glycoside, has recently been suggested to be a novel chemotherapeutic agent. Src is an oncogene that plays an important role in cancer progression and is therefore a potential target for cancer therapy. Here, we investigated whether digoxin could suppress lung cancer progression through the inhibition of Src activity. The effects of digoxin on lung cancer cell functions were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 45 publications
4
52
1
1
Order By: Relevance
“…Given our new data and the reported role of TGF-β in stroma development and metastasis [5658], it is plausible that cardiac glycosides may have anti-cancer activity through downregulation of TGFβR2 in relevant cells. However, while multiple studies have demonstrated the anti-proliferative [24,59] and pro-apoptotic effects [60,61] of cardiac glycosides on various cancer cells in vitro , the effect of cardiac glycosides in the in vivo models of cancer has not been rigorously assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Given our new data and the reported role of TGF-β in stroma development and metastasis [5658], it is plausible that cardiac glycosides may have anti-cancer activity through downregulation of TGFβR2 in relevant cells. However, while multiple studies have demonstrated the anti-proliferative [24,59] and pro-apoptotic effects [60,61] of cardiac glycosides on various cancer cells in vitro , the effect of cardiac glycosides in the in vivo models of cancer has not been rigorously assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed procedures of colony formation assay were described previously [34]. Briefly, 500 cells were resuspended in culture medium and seeded in six-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…14 Itraconazole (an antifungal drug), 15,16 nelfinavir (a competitive inhibitor of the human immunodeficiency virus aspartyl protease), 17 and digoxin (a cardiac glycoside) are some of the drugs that have been explored for their anticancer properties. 18 The repurposed drugs, such as nelfinavir and digoxin, are under investigation in combination with other chemotherapeutic candidates for pancreatic cancer. 19 In the current study, we set out to identify ERK/MAPK pathway-targeting inhibitors from a set of existing drugs for possible targeted therapeutics of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%